Developing Healthy Lifestyle Competencies Through an Elective Course in Psychoregulatory Health-Enhancing Fitness: An Educational Model in Medical Education - Seredovska, Viktoriya; Korostylova, Hanna; Burdin, Igor (Pedagogy and Psychology of Sport, 2026)
Introduction. Regular physical activity is an important determinant of health and an essential component of a healthy lifestyle. Higher education institutions provide an appropriate environment for developing practical competencies that encourage lifelong participation in health-enhancing physical activity. Aim. To describe the educational model, organization, and intended learning outcomes of an elective course in psychoregulatory health-enhancing fitness for undergraduate medical students. Materials and Methods. A descriptive educational study based on curriculum analysis was conducted. The officially approved course syllabus was analysed with respect to educational objectives, course structure, thematic content, teaching methods, intended learning outcomes, and assessment procedures. The analysis was supplemented by the collective teaching experience of the course instructors. Results. The elective course comprises complementary educational components, including Pilates-based exercises, fitness yoga, Body&Mind exercises, breathing exercises, myofascial release techniques, and independent physical activity planning. Rather than teaching individual exercise methods, the course integrates these components into a unified educational model aimed at developing movement competence, body awareness, self-management skills, and healthy lifestyle competencies. The student-centred organization of the course supports practical engagement in health-enhancing physical activity and encourages independent participation beyond the educational setting. Conclusions. The proposed educational model demonstrates that an elective physical education course may serve as an effective educational environment for developing healthy lifestyle competencies through practical experience with different forms of health-enhancing physical activity. The model may be applicable to other higher education programmes seeking to strengthen health promotion within the educational process. Abstract Abridged. This article describes the educational model of an elective course in psychoregulatory health-enhancing fitness developed for undergraduate medical students. Based on curriculum analysis, the paper presents the organization, educational components, and intended learning outcomes of the course. The programme integrates Pilates-based exercises, fitness yoga, Body&Mind activities, breathing exercises, myofascial release techniques, and independent physical activity planning within a student-centred educational framework. Rather than emphasizing mastery of individual exercise methods, the course focuses on developing healthy lifestyle competencies, movement competence, body awareness, self-management, and sustainable participation in regular health-enhancing physical activity. The proposed educational model may also be relevant for other higher education programmes promoting healthy lifestyle behaviours.